Case Report: Optic neuritis as the initial presentation of Orientia tsutsugamushi infection detected by metagenomic next-generation sequencing - Sun, Chuan-bin; Ma, Zhiqiong; Liu, Zhe (Frontiers in Immunology, 2023)
Scrub typhus is an acute febrile illness caused by Orientia tsutsugamushi infection, and typically manifested as fever, eschar, lymphadenopathy, rash, and other flu-like signs. Ocular involvement was not uncommon, and mostly occurred at post-fever or recovery stage in scrub typhus cases. We hereby report a case of scrub typhus presenting as unilateral optic neuritis (ON). A 56-year-old man going wild fishing nearly every day complained of a blurred vision and an inferior visual field defect in the right eye two or three days after an insect-bite like shin induration in his left leg. He was diagnosed as ON, and treated with dexamethasone in the local hospital. Unfortunately, his right eye vision progressively deteriorated during steroid therapy. Three days after steroid therapy ceased, he suffered from a high fever and painful subcutaneous masses in the left groin. Peripheral blood test by metagenomic next-generation sequencing (mNGS) was positive for Orientia tsutsugamushi, but negative for other pathogens. The diagnosis was then revised to scrub typhus and ON. His systemic symptoms rapidly disappeared after oral doxycycline and omadacycline therapy. However, his right eye vision continuously deteriorated to hand motion. Further serum tests for aquaporin 4-IgG antibody and myelin oligodendrocyte glycoprotein-IgG antibody were both negative, but for anticardiolipin IgM and beta-2-glycoprotein-I IgM were both positive. The patient’s right eye vision gradually improved after doxycycline combined with steroid pulse therapy. Our case indicates that ON in scrub typhus cases may present as a parainfectious inflammation, and that mNGS is a useful and valuable method for early diagnosis of scrub typhus.